2022
DOI: 10.1002/sd.2357
|View full text |Cite
|
Sign up to set email alerts
|

A balancing act between economic growth and sustainable development: Historical trajectory through the lens of development indicators

Abstract: The evolution of the development discourse is profoundly political. Despite a range of innovations the situation remains much the same, and has led over time to the dominance of the economic growth model. Whilst academic/ideological vigour, policy relevance and institutional support, together with intellectual independence, are essential; too radical an alternative approach would be dismissed by mainstream opinion, either by design or neglect. To survive and to remain influential, any alternative requires the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 75 publications
1
14
0
1
Order By: Relevance
“…This conclusion is consistent with the results of Derwall et al (2005), Friede et al (2015), and so forth. In addition, the findings of this paper demonstrate the trend of the study in this direction (Hirai, 2022; Mazzeo, Baglivo, et al, 2021) and provide evidence for industry‐level experience (ElAlfy et al, 2020; Elkadeem et al, 2022; Herdem et al, 2020; Mazzeo et al, 2020; Mazzeo, Herdem, et al, 2021) from a capital market perspective. Table 1 shows the brief literature summary.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…This conclusion is consistent with the results of Derwall et al (2005), Friede et al (2015), and so forth. In addition, the findings of this paper demonstrate the trend of the study in this direction (Hirai, 2022; Mazzeo, Baglivo, et al, 2021) and provide evidence for industry‐level experience (ElAlfy et al, 2020; Elkadeem et al, 2022; Herdem et al, 2020; Mazzeo et al, 2020; Mazzeo, Herdem, et al, 2021) from a capital market perspective. Table 1 shows the brief literature summary.…”
Section: Introductionsupporting
confidence: 68%
“…The study contributed the existing literature in the following three ways: First, the study confirmed the firms' sustainable development strategies both have positive effects (Hirai, 2022;Huan et al, 2022;Rafique et al, 2022) and negative effects (Antal & Van Den Bergh, 2016;Chetty et al, 2015;Hickel & Kallis, 2020) on their performances. Second, the study went on step further (Bauer et al, 2005;Othman, 2012) to prove that the economic benefits generated from the firms' sustainable development strategies could be explained by stochastic volatility, jump risk, short selling restrictions, and arbitrage risk effects.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The simplest attempts to capture this discursive terrain distinguish between ‘weak sustainability’, which is characterised by the assumption that natural capital is infinitely substitutable with human capital and that technological innovation will solve all ecological problems; and ‘strong sustainability’, which is sceptical of both these claims (e.g. Ayres et al, 2001; Hirai, 2022; Neumayer, 2003). Other bipartite taxonomies include the juxtaposition of ‘anthropocentric’ and ‘ecocentric’ sustainability (e.g.…”
Section: Methods: a Framework For Analysing Sustainable Development A...mentioning
confidence: 99%
“…Sustainable urban mobility requires the need to develop new indicators (Morfoulaki and Papathanasiou, 2021). Indicators make it possible to describe trajectories of sustainable development, identify appropriate policies, and measure performance (Alola et al, 2021; Hirai, 2022). Achieving carbon neutrality requires long‐term environmental strategies (Abbasi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%